Content of Fluoride in Bottled Mineral Waters Sold in Japan - Tanida, Eri; Suzuki, Shinichi; Yamamoto, Kimiyo; Ohnishi, Keiko; Takasaki, Kyosuke; Tsuji, Hiroshi; Kono, Koichi; Usuda, Kan; Imanishi, Masafumi (BIOMEDICAL RESEARCH ON TRACE ELEMENTS, 2008)
The content of fluoride, calcium and magnesium was determined by means of a fluoride ion selective electrode and inductively coupled plasma atomic emission spectroscopy in thirty-three brands of bottled mineral waters sold in the Japanese market. The geometric means of fluoride, calcium and magnesium were 79.8 μg/l, 19.1 μg/l and 2.8 μg/l, respectively. The fluoride content of Japanese and European brands was significantly higher than that of other brands. The calcium and magnesium concentrations were higher in the European brands than in all other brands. Simple linear regression and multiple linear regression analysis show that calcium and fluoride reach mineral water simultaneously. Our results show that only two brands imported from France and Italy exceed the World Health Organization's guideline value of 1.5 mg/l. All of the other samples analyzed contain less than 10% of that value. We also found that the fluoride intake of Japanese adults from mineral water is only 0.018-2.14% of the National Research Council upper recommended intake of 1.5-4.0 mg/day. Bottled mineral water can be considered as a source of fluoride but most brands are not a risk for fluorosis. However, sensitivity to fluoride depends on the subject's general health and age. To minimize the potential risk of exposure posed by mineral water the fluoride content should be fully disclosed on the label.